Does the Clean Development Mechanism Exist in Developing Countries After an International Agreement? - Nihayah, Dyah Maya; Gravitiani, Evi; Rahayu, Siti Aisyah Tri (International Journal of Energy Economics and Policy, 2021)
The Kyoto Protocol is a key document on climate change agreements by the United Nations Framework on Climate Change. The latest commitments agreed in 2012. Its agreed to reduce CO2 emissions by about 20% or less of all global carbon emissions. A strong commitment is needed to reduce greenhouse gas emissions by governments from various countries. This study aims to figure out the progress of clean development mechanism of reducing CO2 emissions in the Asia and Middle East Region countries after the Kyoto Protocol Commitment. Variable CO2 emissions, economic growth, foreign direct investment, trade activities which covered from 2013 to 2017 were analysed using a panel data model. The alteration after agreement were evaluated using a Klassen Typology. The results show that economic growth and trading activities have a significant effect on clean development mechanism in Asia and the Middle East, but still have differences in the patterns and behavior of each country in implementing commitments to reduce CO2 emissions. Overall, attempts are needed to align economic growth with efforts to reduce emissions so that prudent policies are needed in forming realistic and sustainable mitigation and adaptation steps to address the problem of climate change. Keywords: CO2 emission, clean development mechanism, agreement, Klassen Typology, mitigation JEL Classifications: Q5, Q28, Q54, Q540 DOI: https://doi.org/10.32479/ijeep.11514